Evidence of Optical Circular Dichroism in GaAs‐Based Nanowires Partially Covered with Gold. Issue 16 (7th March 2017) - Leahu, Grigore; Petronijevic, Emilija; Belardini, Alessandro; Centini, Marco; Sibilia, Concita; Hakkarainen, Teemu; Koivusalo, Eero; Rizzo Piton, Marcelo; Suomalainen, Soile; Guina, Mircea
Abstract : Semiconductor nanostructures hybridized with metals have been known to offer new opportunities in nonlinear optics, plasmonics, lasing, biosensors; among them GaAs‐based nanowires (NWs) hybridized with gold can offer new functionalities, as chiral sensing and light manipulation, as well as circular polarization sources. This study investigates GaAs–AlGaAs–GaAs NWs fabricated by self‐catalyzed growth on Si substrates, and partially covered with gold, thus inducing the symmetry breaking and a potential chiral response. Three different samples are investigated, each of them with a different morphology, as the length and the overall diameter ranging from 4.6 to 5.19 µm and from 138 up to 165 nm, respectively. The samples are first characterized by measuring the absorption spectra by using a scattering‐free photoacoustic (PA) technique. Then, the circular dichroism (CD) is investigated by measuring PA absorption for circularly polarized light under different incident angles at 532 and 980 nm. An efficient CD is found for proper configurations, and results are in good agreement with extrinsic chiral theory predictions and numerical simulations. It is therefore proven that these samples exhibit chiral behavior, and can be further optimized. Moreover, PA technique can be used as an extremely sensitive and efficient technique to characterize their "extrinsic" chirality. Abstract : GaAs–AlGaAs–GaAs nanowires (NWs) with asymmetric gold covering put in interaction with circularly polarized light mimic a chiral response measured by photoacoustic absorption technique. Bringing together the advantages of good optical properties of vertical NWs and "extrinsic" chiral behavior leads to the new perspectives in control of the light at nanoscale.